Pengaruh Integrasi Artificial Intelligence terhadap Kesiapan dan Persepsi Praktisi Pendidikan Jasmani di Indonesia - Toho Cholik Mutohir; Zetiawan Trisno; Danang Ari Santoso; Fekie Adila; Fansah Adila; Mega Permata Sari (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study analyzes the influence of AI integration on the readiness and perceptions of Physical Education (PE) practitioners in Indonesia, a topic not yet comprehensively mapped. A cross-sectional survey was conducted with 352 respondents (undergraduate students, teachers, graduate students, lecturers). The instrument, based on the Technology Acceptance Model (TAM), assessed demographics, AI knowledge, perceived benefits and risks, and readiness. Data were analyzed using descriptive statistics, non-parametric tests, and Spearman correlation. Respondents demonstrated high AI exposure (86.4%). Perceived benefits (mean=4.15±0.67) and risks (3.98±0.71) were both high. A significant paradox emerged: personal readiness was very high (4.29±0.61), while institutional readiness was low (3.74±0.89). Significant differences in risk perception were found based on respondent status (p=0.043). AI knowledge positively correlated with perceived benefits (r=0.18), personal readiness (r=0.24), and innovation support (r=0.26) (all p<0.01). Indonesian PE practitioners exhibit high personal readiness for AI integration, yet this is significantly hindered by low institutional preparedness. Policy priorities should focus on enhancing infrastructure, conducting mass AI literacy training, and establishing data protection regulations.